2015
DOI: 10.1111/1346-8138.12772
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony‐stimulating factor‐induced granulomatous dermatitis with enlarged histiocytes clinically manifesting as painful edematous nodules with high fever similar to Sweet's syndrome

Abstract: A 72-year-old woman with a history of diffuse large B cell lymphoma and recent recurrence visited our department complaining of several painful edematous nodules with blisters on her face. She had iteratively developed cutaneous eruptions after every treatment with granulocyte colony-stimulating factor (G-CSF) for neutropenia, and each time the eruption improved after the cessation of the G-CSF treatment. The blisters became crusty and the skin lesions slightly improved, but on the 24th hospital day, the erupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, in later years, very few reports of the psoriasis-like eruption were reported in the literature. Rather other forms of G-CSF induced drug eruptions were reported such as generalized erythematous and indurated papules and plaques with mild epidermal spongiosis and dermal infiltrate of enlarged plump macrophages, granulomatous dermatitis with enlarged histiocytes clinically manifesting as painful edematous nodules with high fever similar to Sweets syndrome, and cases of G-CSF induced Sweet syndrome reported by Kenneth et al and White et al [2,[8][9][10][11]. It has also been reported that G-CSF stimulates the proliferation of myeloid leukemic cells.…”
Section: Discussionmentioning
confidence: 94%
“…However, in later years, very few reports of the psoriasis-like eruption were reported in the literature. Rather other forms of G-CSF induced drug eruptions were reported such as generalized erythematous and indurated papules and plaques with mild epidermal spongiosis and dermal infiltrate of enlarged plump macrophages, granulomatous dermatitis with enlarged histiocytes clinically manifesting as painful edematous nodules with high fever similar to Sweets syndrome, and cases of G-CSF induced Sweet syndrome reported by Kenneth et al and White et al [2,[8][9][10][11]. It has also been reported that G-CSF stimulates the proliferation of myeloid leukemic cells.…”
Section: Discussionmentioning
confidence: 94%
“…is postulate is supported by the fact that serum G-CSF level has been shown to correlate directly with disease severity in many patients. [5][6][7] e finding of dermal neutrophils exhibiting genetic abnormalities similar to malignant myeloblast in bone marrow has led to the postulate that these cells arise as a result of the clonal transformation of dysplastic neutrophils. Infection-and drug-induced SS is thought to be secondary to a cytokine cascade stimulated by an inciting agent.…”
Section: Discussionmentioning
confidence: 99%
“…[8,12] e most common malignancy associated was AML seen in 16 patients, followed by chronic myeloid leukemia in blast crisis and myeloproliferative disorder in one patient each. [7,8,12] Other rarer causes were congenital agranulocytosis and Fanconis anemia seen in 3, 1 patients simultaneously. [13][14][15] Most of these patients had received G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…The CSF3 gene (aka GCSF) encodes a protein with many immunological roles, such as survival, proliferation, and polarization of macrophages (Hollmén et al 2016;Wen et al 2019); it has also been detected in multiple macrophage infection studies using pathogenic MTBC strains (Malone et al 2018;Papp et al 2018;Hall et al 2020). Although it has been shown to be upregulated in sarcoidosis granulomas (Casanova et al 2020), the role of CSF3 in TB-induced granuloma formation has not been extensively studied; however, induction of granulomatous tissue by CSF3 has been documented in other conditions, such as granulomatous dermatitis and chronic granulomatous disease in immunocompromised patients (Sekhsaria et al 1996;Ozaki et al 2015). However, it is important to note that colony stimulating factor proteins have recently been shown-in a membrane fusion-independent manner-to stimulate the formation of multinucleated giant cells (MGCs), which are key components of TB-induced granulomas.…”
Section: Genes Enriched For Btb and Htb Gwas Snps In Both Species Pla...mentioning
confidence: 99%